2018
DOI: 10.1007/s13337-018-0434-8
|View full text |Cite
|
Sign up to set email alerts
|

Viruses infecting macrofungi

Abstract: Ever since their discovery just about 56 years ago in the cultivated mushroom , many more viruses infecting fungi have been identified in a wide range of fungal taxa. With mostly being asymptomatic, especially the ones that are detrimental to their phytopathogenic hosts are intensively studied due to their considerable importance in developing novel plant protection measures. Contrary to the rapid accumulation of notable data on viruses of plant pathogenic microfungi, much less information have hitherto been o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 84 publications
0
13
0
Order By: Relevance
“…Mycoviruses (fungal virus) are the viruses that specifically infect fungi and many of them have RNA as their genetic material [ 53 ]. Using the positive strand RNA of Tobacco Mosaic Virus (TMV) as a model, Citores et al demonstrated that Ageritin is able to promote an extensive degradation of the polyphosphate RNA backbone and therefore to increase its mobility [ 52 ].…”
Section: Enzymatic Properties Of Ageritinmentioning
confidence: 99%
“…Mycoviruses (fungal virus) are the viruses that specifically infect fungi and many of them have RNA as their genetic material [ 53 ]. Using the positive strand RNA of Tobacco Mosaic Virus (TMV) as a model, Citores et al demonstrated that Ageritin is able to promote an extensive degradation of the polyphosphate RNA backbone and therefore to increase its mobility [ 52 ].…”
Section: Enzymatic Properties Of Ageritinmentioning
confidence: 99%
“…Although speculative, the absence of spores might help explain the stability of the variety. Spores are a known vector for viral diseases in macrofungi [ 54 ] including P . ostreatus [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 3D structures for the phytochemicals were obtained from PubChem ( https://pubchem.ncbi.nlm.nih.gov/ ). The pharmacological and pharmacokinetic properties based on parameters of ADMET (Absorption, Distribution, Metabolism, Excretion and Toxicity) were evaluated with the help of the SwissADME web server [ 38 ] and PreADMET server [ 39 ], as reported in [ 23 , 26 , 28 , 29 , 31 ]. SwissADME server was utilized for the determination of ADME properties of the phytochemicals, while PreADMET was utilized to assess the druglikeness features and toxicity level of the drug.…”
Section: Methodsmentioning
confidence: 99%